An improved contact model considered the effect of boundary lubrication regime on piston ring-liner contact for the two-stroke marine engines from the perspective of the Stribeck curve. (March 2022) - Xiuyi, Lyu; Jiao, Bowen; Wang, Yuechang; Azam, Abdullah; Lu, Xiqun; Zou, Dequan; Ma, Xuan; Neville, Anne
The prediction of lubrication performance is required to be the basement of friction optimization for marine engines. This paper simulates the lubrication performance of marine engines based on statistical models which have the advantages of fast, efficient, and macroscopic fault location. Boundary lubrication exists in the piston ring-cylinder liner (PRCL) of two-stroke marine engines because of the harsher load, lower speed, and larger structure. It has been proposed that there would be tribofilm under boundary lubrication which has a significant influence on the contact. To understand the boundary lubrication, it is necessary to study the lubrication regime transition. In this paper, firstly, the coefficient of friction curve combined with the thickness ratio embodies the lubrication regime transition process of two-stroke engines under work conditions. However, the phenomenon that the coefficients under boundary lubrication are smaller than that of other regimes shows the non-objectivity of this curve. Therefore, the Stribeck curve is introduced for objectively evaluating the transition. Then, the calculation of asperities contact pressure under boundary lubrication, which Wen proposed, is introduced into the classic Greenwood-Williamson model, the problem that the original model cannot reflect the boundary lubrication regime in the form of the Stribeck curve is improved. Finally, the results are compared before and after modifying the model to verify this study's practicability. It provides more precise asperities contact pressure for the tribofilm growth calculation from the perspective of the Stribeck curve under the PRCL statistical model in future work.